Results of the ‘Reading in the Time of War’ Target Survey of Teenage Bloggers - Olena Ryzhko (Youth in Central and Eastern Europe, 2022)
The goal of the ‘Reading in the Time of War’ survey of teenagers was the need to find out the opinions of young book bloggers about what reading is for them now, in the conditions of the full-scale invasion of Russia in Ukraine: a way to normalize the world, an escape from a terrible reality, a means of gaining popularity, or something else. The survey was conducted from July 21 to August 10, 2022, by the method of purposive sampling using Google Forms. It covered 45 bloggers who live in Ukraine or were forced to evacuate abroad. The results showed that for those who like to read, books remain a way (often the only possible) of normalizing the world and getting salvation, an escape from the terrible reality under any force majeure circumstances. Genre literature is in constant demand among teenagers: fantasy/sci-fi, detective, and adventure. Realistic prose became more popular. In addition, teenagers use their own blogs to tell the truth about the war in Ukraine and popularize Ukrainian literature/culture around the world.